ChemInform Abstract: One‐Pot Synthesis of Indoles from Alkynes and Anilines Through Palladium‐Catalyzed Double C—H Activation Using O2 as the Oxidant. Issue 25 (2nd June 2016) - Shi, Dunfa; Guan, Zhipeng; Yao, Xiuwen; Shi, Wei; Chen, Hao
Abstract: One‐pot synthesis of substituted indoles from cyanoalkynes and anilines through Palladium catalyzed double C—H activation is successfully developed.